Vascular Grooves on Human Femora and Tibiae as a Potential Activity‐related Trait. (12th November 2012) - Sołtysiak, A.
Abstract The presence of vascular grooves on the shafts of femora and tibiae was scored for a sample of human remains from a mass burial at Tell Majnuna, Syria, dated to the early fourth millennium bce. In the sample of 140 femora and 64 tibiae, many of which were damaged or fragmented, the grooves were most common on the femoral midshaft (31/108 = 28.7%) and on the proximal and middle shaft of the tibia (10/45 = 22.2 and 14/54 = 26.0%, respectively). For femoral midshafts, the difference in mean cross‐sectional size and shape indices between bones with and without vascular grooves was checked with multivariate analysis of variance for a sample of 51 bones. The presence of grooves appeared to correspond significantly with higher mean values of both indices. As the shape index is interpreted as an indicator of the level of terrestrial mobility and the size index may be used for sex assessment, it is possible that vascular grooves occur more frequently at the femoral midshafts of men and more active individuals, and thus they may be cautiously interpreted as another activity‐related trait. Copyright © 2012 John Wiley & Sons, Ltd.